Booklets as a Community Based Education Related To Child Development for Kotaanyar Community, Probolinggo - Lailatul Fitriyah; Zaini Gunawan; Tristan Rokhmawan (EDUTEC : Journal of Education And Technology, 2020)
In the context of the availability of literacy sources about early childhood development, the people of Kotaanyar District, Probolinggo Regency are constrained by limited access and understanding. The limited access in this case is the limitation in finding main literacy sources such as books and online literacy content. The limitation of understanding in this case is the difficulty of them (parents of early childhood) to understand content that contains scientific and technical concepts regarding information on children's development. This is due to the low participation rate in taking education in this area. With this problem, researchers conducted research & development of booklets with stimulus content for early childhood growth and development which were made in such a way as to be completed with pictures and by using simple exposures, direct practice, and local language. The content developed is divided according to the stages of developmental age and children's growth, ages 0-12 months, 12-24 months, 24-36 months, 36-48 months, pre-school age 48-60 months. The development of stimulation content is divided based on general information on growth and developmental aspects including aspects of motoric physical development, aspects of cognitive development, aspects of language development, aspects of social emotional development. As a basis for development, we use some references related to children's accumulation strategies from several books, the rest we add stimulus content on the basis of child development problems that were found in a typical and contextual manner in the Kotaanyar District community. Presentation in bilingual form is needed so that it can be understood by the local community, who mostly speak the Madura Pendalungan area (slightly different from the language of the island Madurese / origin Madurese). Therefore, after the content and illustration development stage, the researcher translated the booklet into the Madurese Pendalungan language. This is solely done to facilitate understanding of the local community, and also to facilitate early childhood education coaches / socializers to explain in the local language. Finally, we need to package a booklet with an attractive and illustrated layout to serve as an illustration of the child's stimulation activity.